Optimization of sprint training among European coaches: Quality over quantity - Agudo-Ortega, A.; Sandbakk, Ø.; Salinero, J. J.; Johansen, B.; González-Rave, J. M. (International Journal of Sports Physiology and Performance, 2024)
Purpose To describe how high-level European sprint coaches (from 100 to 400 m) work to improve important factors associated with the quality of the holistic training process and the quality of the specific training session.